2019
DOI: 10.1080/09505431.2019.1597035
|View full text |Cite
|
Sign up to set email alerts
|

Science Communication as Emotion Work: Negotiating Curiosity and Wonder at a Science Festival

Abstract: STS scholarship has long emphasised that science is emotional as well as cognitive and social. A 2014 science festival, Science in the City, held in Copenhagen, provides a case for thick description of emotion within the production and reception of public science communication. For organisers of science communication the overarching aim was to call forth a suite of emotions focused around curiosity and wonder; in contrast, visitor experiences were constituted through the emotions of reading and negotiating sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 41 publications
2
28
0
4
Order By: Relevance
“…McPhetres, 2019; Valdesolo et al, 2017). This corresponds to the intuition held by many in science communication who have assumed that awe and wonder enhance people’s interest in the subject (Davies, 2019). A small body of evidence supports this interpretation.…”
Section: The Classical View Of Awe In the Communication Of Sciencesupporting
confidence: 71%
“…McPhetres, 2019; Valdesolo et al, 2017). This corresponds to the intuition held by many in science communication who have assumed that awe and wonder enhance people’s interest in the subject (Davies, 2019). A small body of evidence supports this interpretation.…”
Section: The Classical View Of Awe In the Communication Of Sciencesupporting
confidence: 71%
“…Both the judgment of risk and emotion are in flux and not confined to the individual (Lupton 2013). Furthermore, some STS scholars stress that emotions are a crucial element of public engagement, deliberation and science communication (Davies 2014(Davies , 2019.…”
Section: Emotion-friendly Approachesmentioning
confidence: 99%
“…Learning, and the pleasures of (self) education, seem particularly key. Less positively, users may report confusion, boredom, or frustration [Davies, 2019]. Indeed, some individuals may experience emotions of exclusion or isolation: recent work has shown that science communication continues to be implicitly designed with specific audience groups (generally those who are already well-served) in mind, leaving others with the sense that it is something that is 'not for us' [Burns and Medvecky, 2016;Dawson, 2014].…”
Section: Science Communication As Emotionalmentioning
confidence: 99%